Pendampingan Pembuatan Laporan Keuangan Sederhana Usaha Laundry Di Dusun Bokoharjo Rt 06 Kelurahan Maguwoharjo Depok Sleman - Sudyartini; Astuti, Tutut Dewi (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2023)
Based on the results of questions and answers with home laundry business owners, it is known that they cannot show directly how much profit their business earns each month because there is no separate bookkeeping from household finances. This activity aims to provide knowledge about simple financial reports so that business actors can separate profits/losses from their business activities from personal finance. This method is done through question and answer, socialization, and mentoring. During the question and answer session, it became clear that the obstacle for business actors is a lack of understanding of basic accounting. Based on this initial identification, it is very appropriate to provide training and assistance in preparing simple financial reports. Because the business actors are housewives unfamiliar with information technology, the authors use a lined folio book to make handwritten notes during the training. Following participant transactions, the training is conducted in groups and separately performed.